Praca ważna i doniosła - Moczkodan, Rafał (Tematy i Konteksty, 2015)
‘To save the home country from migrational distance… Lithuanian art and Lithuanian artists on emigration (1940-1990)’ (Moscow 2012) focuses on stressing the importance of the work under discussion. First and foremost, it should be pointed out that it is the first synthesis encompassing such an extensive subject, which has not thus far been examined. It is also emphasized in the review that the composition of the work as well as its abundance in content are worth noting (230 profiles of Lithuanian painters and graphic artists are presented). Additionally, we should appreciate the methodological values and the diligence of the author in research. On the other hand, the lack of illustrative material seems to be a drawback of the work. All in all, the work is highly assessed.